2020
DOI: 10.1136/vr.105525
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma hyopneumoniae in nasal and laryngeal swab specimens in endemically infected pig herds

Abstract: BackgroundApparently, laryngeal swabs (LS) are more sensitive than nasal swabs (NS) and allow earlier detection of Mycoplasma hyopneumoniae by PCR. However, antecedents about the compared detection of M hyopneumoniae with NS and LS in growing pigs, from naturally infected herds, are lacking in the literature. Thus, this study compared the PCR detection of M hyopneumoniae from NS and LS in pigs of various ages.MethodsA longitudinal study was performed at two farms where NS and LS were collected from three conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition to PCV2 and PCV3 detection, according to the different symptoms of the clinical cases from which the samples were derived, porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), porcine rotavirus (PoRV), porcine transmissible gastroenteritis virus (TGEV), porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV) and (MHP) were also detected. The assays used were as described previously ( 23 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to PCV2 and PCV3 detection, according to the different symptoms of the clinical cases from which the samples were derived, porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), porcine rotavirus (PoRV), porcine transmissible gastroenteritis virus (TGEV), porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV) and (MHP) were also detected. The assays used were as described previously ( 23 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…8,[28][29][30][31] Furthermore, the lower respiratory tract represents the natural site of M. hyopneumoniae multiplication, 32 whereas the nasal mucosa may only be transiently colonised before M. hyopneumoniae reaches the lower respiratory tract. 33 Particularly, tracheobronchial swabbing seems to be suitable for M. hyopneumoniae detection, since sensitivity of detection by PCR turned out to be at least as high as that of tracheobronchial washing. 28 Moreover, tracheobronchial swabs (TBS) are less time-consuming and cost-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, in several studies, samples from the lower respiratory tract revealed a higher sensitivity than swabs from the nasal cavity 8,28–31 . Furthermore, the lower respiratory tract represents the natural site of M. hyopneumoniae multiplication, 32 whereas the nasal mucosa may only be transiently colonised before M. hyopneumoniae reaches the lower respiratory tract 33 . Particularly, tracheobronchial swabbing seems to be suitable for M. hyopneumoniae detection, since sensitivity of detection by PCR turned out to be at least as high as that of tracheobronchial washing 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Nasal swabs have demonstrated use in the surveillance of various porcine respiratory pathogens, including Mycoplasma hyopneumoniae ( 45 , 46 ), porcine circoviruses ( 47 50 ), parainfluenza virus ( 51 , 52 ), influenza A virus ( 24 , 25 , 53 ), Pasteurella multocida ( 54 , 55 ), Actinobacillus pleuropneumoniae ( 56 ), and PRRSV ( 18 ). The use of oral swabs in surveilling swine respiratory pathogens has not gained as much traction as its more passively obtained counterpart, the oral fluid sample ( 57 ).…”
Section: Discussionmentioning
confidence: 99%